Development and validation of facebook reels in teaching the vocabulary of Senior High School students - Alcantara, Rafaela Marie A.; Dela Cruz, Margerie Q.; Escobal, Ma., Ahlea E.; Lacanilao, Wennah Sula V.; Mata, Christine Je-Ann (b)
This quasi-experimental study, grounded in constructivist theory, investigates the development and validation of Facebook Reels as an innovative tool for enhancing vocabulary acquisition among senior high school students. Given the pervasive use of social media platforms among adolescents, integrating familiar digital content into educational practices offers a promising approach to language learning A total of 40 senior high school students participated in the study, divided into a control group and an experimental group. Both groups underwent pre- and posttest to measure vocabulary knowledge. The control group achieved a mean score of 13.45 on the pretest and 13.85 on the posttest, indicating minimal improvement. In contrast, the experimental group recorded a mean score of 14.80 on the pretest and 26.30 on the posttest, demonstrating a significant increase in vocabulary acquisition. These results suggest that exposure to Facebook Reels, which feature context- rich vocabulary in engaging formats, can effectively enhance students{92} vocabulary skills. To gain deeper insight into students{92} experiences ,the study incorporated qualitative data collected through Google Form-based interviews. Thematic analysis of the response revealed that students found the Reels videos engaging and informative, with many reporting increased motivation to learn new words. Students appreciated the visual and auditory element of the videos,which facilitated better retention and understanding of vocabulary. Additionally, the short duration of the Reels aligned well with students{92} attention spans,making learning more accessible and enjoyable. The findings from both the quantitative and qualitative components underscore the potential of integrating social media platforms like Facebook Reels into educational practices to support vocabulary development in the digital age. This study contributes to the growing body of literature on digital literacy and language acquisition, highlighting the effectiveness of multimedia tools in enhancing language learning outcomes
Undergraduate thesis